Effects of welding parameters on percentage dilution and mechanical properties in welded joints of ultra-high hardness armour steels - DE VASCONCELOS, CHARLES; LE SÉNÉCHAL, NAIARA; LOAYZA, CRISTHIAN; FILHO, ADEMIR; BRAGA, EDUARDO; PAULA, ANDERSAN; WEBER, RICARDO (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
This study investigates the effects of Gas Metal Arc Welding (GMAW) parameters—specifically welding speed and stick-out—on the dilution and mechanical properties of welded joints composed of ultra-high hardness quenched and tempered (UHH-Q&T) armor steel and austenitic stainless steel filler metal. An optimization methodology was used to set constant parameters, including wire diameter, gas flow rate, welding voltage, and wire feed speed, based on equipment capabilities. Experimental trials varied welding speed and electrode stick-out while maintaining a constant current through inductance control. Although the welding parameters affected the melted base and filler metal areas, the dilution percentage remained unaffected. The correlation between dilution and welding current was validated. Microstructural and mechanical analyses confirmed the consistent behavior of the welded joints under the tested conditions.